2014
DOI: 10.1080/00288233.2014.978482
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for milk components including lactose from test day records in the New Zealand dairy herd

Abstract: There are currently few published estimates of genetic parameters for lactose yield or lactose percentage for dairy cows. Recent trends in milk standardisation for whole milk powder have resulted in whole milk being standardised with the ratio of protein to protein-plus-lactose of at least 0.39. Currently whole milk powder produced from New Zealand milk has a protein to protein-plus-lactose ratio of 0.43, thus requiring additional lactose to be imported to maximise the return from the current product portfolio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
33
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 14 publications
22
33
6
Order By: Relevance
“…Phenotypic correlations found in this study (table 3) are much different than those of Sneddon et al (2015) who reported phenotypic correlations among milk yield and fat and protein yield of 0.75 and 0.92, respectively. Similar findings, for pure bred Holstein cows, were reported by Elzo et al (2004) where the correlations, in the same order, were estimated at 0.82 and 0.88.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Phenotypic correlations found in this study (table 3) are much different than those of Sneddon et al (2015) who reported phenotypic correlations among milk yield and fat and protein yield of 0.75 and 0.92, respectively. Similar findings, for pure bred Holstein cows, were reported by Elzo et al (2004) where the correlations, in the same order, were estimated at 0.82 and 0.88.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are very close to the average between estimates of Lembeye et al (2016 b ) for fat and protein yield (0.25±0.010), and fat and protein percentage (0.66±0.009). Sneddon et al (2015) found heritabilities, for fat and protein percentage, at 0.35±0.05 and 0.32±0.05, respectively, which are lower than the estimates presented in this research. The estimates of Elzo et al (2004) for fat and protein yield in Chilean cows ranged from 0.29 to 0.37 and 0.17 and 0.24, respectively.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…Genetic gain per year was predicted to remain as published by NZAEL (2013) at 44 L of milk, 2.22 kg fat, 1.82 kg protein and −0.039 kg live weight for the 2013-2014 dairy season. Genetic gain in lactose percentage was assumed to be unchanged by selection on BW, this was assumed from the high genetic correlation (0.98-0.99 between milk and lactose yields) (Hossein-Zadeh & Ardalan 2011; Miglior et al 2007;Sneddon et al 2012Sneddon et al , 2014cWelper & Freeman 1992), which resulted in lactose gains of 2.07 kg per year, which is 4.7% of the 44 L gain in milk yield. Improvement of productive performance caused by better feeding, supplementary feeding or management was not considered in the simulation.…”
Section: Genetic Gains and Expected Cow Performancementioning
confidence: 99%